Policy Interventions to Overcome the Impact of Covid 19 on Employment in the Tourism Sector - Herbasuki Nurcahyanto (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2021)
The Covid 19 pandemic (PC 19), which has spread to various parts of the world, has led to a decline in the world economy and an increase in unemployment in all sectors including the tourism sector. The government has taken various policies in overcoming PC 19, namely Large-Scale Social Restrictions (PSBB) and various other policies that have increasingly caused the deterioration of the tourism sector. Workers who work in the tourism sector are affected by this policy. Many of them were affected by layoffs or the closing of businesses that had been operated for a long time. The purpose of this research is to provide policy advice to the government in order to immediately solve the problem of unemployment, especially in the tourism sector. This study uses a qualitative approach with library data collection methods (desk research). The government with all managed resources are be able to generate quality tourism. The government are able to collaborate with all stakeholders to be able to lift the tourism sector and save workers from a prolonged economic downturn. Collaboration can be realized in a pentahelix model that involves academics, business, community, government and the media.